The Interaction of Feelings: Delving into the Depths of Happiness and Sorrow - Begoyim Abdusattorova (Open Academia, 2024)
This article delves into the complex connection between joy and sadness, two essential human emotions. It investigates how these emotions coexist and interact, their temporary nature, and their capacity to facilitate personal development. Furthermore, it analyzes the attributes and impacts of joy and sadness on individuals and their interactions within society
Keywords: Feelings; happiness; sorrow; interaction